Dukungan Organisasi dan Motivasi Kerja dengan Mediasi Inovasi Layanan terhadap Kinerja Pemasaran Berbasis Pengalaman - Yusuf, Ludwi; Amalia, Dinda (Awatara Publisher, 2026)
This study examines the influence of organizational support and work motivation on experiential marketing performance through the mediating role of service innovation among Micro, Small, and Medium Enterprises (MSMEs) in Purwakarta, Indonesia. Drawing upon Service Innovation Behavior Theory, the study explores how organizational and individual factors contribute to customer-oriented marketing outcomes through innovation processes. A quantitative research design was employed using a cross-sectional survey approach. Data were collected from 312 MSME owners and managers and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that organizational support significantly enhances service innovation. Work motivation also positively influences service innovation, suggesting that motivated individuals are more likely to engage in innovative service activities. Furthermore, service innovation exerts a significant positive effect on experiential marketing performance. The mediation analysis reveals that service innovation significantly mediates the relationships between organizational support and experiential marketing performance as well as between work motivation and experiential marketing performance. These findings confirm the central role of service innovation in transforming organizational resources and employee motivation into superior customer experiences. The study contributes to the service innovation and experiential marketing literature by providing empirical evidence from the MSME context and offers practical implications for improving organizational competitiveness through innovation-driven customer experiences.